TikTok Application as A Media for Learning Indonesian Language in Elementary Schools - Kemal, Faisal; Hikmat, Ade; Safi’i, Imam (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This study aims to describe the use of TikTok as a learning tool for Indonesian language in elementary schools, aligning with the current digital era. Social media, including TikTok, attracts millennials and can serve as an engaging learning platform. TikTok's popularity makes it a potential medium for fun and interactive education. The use of TikTok in learning aims to facilitate both students and teachers. This research uses literature review. The data were taken from articles that discussed relevant topic that is about TikTok as a learning media. The gathered data is then reduced to draw relevant conclusions. This research demonstrates that TikTok, when used with appropriate methods, can be an alternative and effective tool for studying Indonesian language. The results indicate that TikTok's ease of use and various features make it a practical resource for interactive learning in elementary schools. Thus, TikTok can be a valuable aid in enhancing Indonesian language education through innovative digital approaches.